2018
DOI: 10.1080/14693062.2018.1527677
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptation and development as usual? Investigating climate change mitigation and adaptation projects in Cambodia

Abstract: Based on research into multiple types of climate change mitigation and adaptation (CCMA) projects and policies in Cambodia, this paper documents intersecting social and environmental conflicts that bear striking resemblance to well-documented issues in the history of development projects. Using data from three case studies, we highlight the ways that industrial development and CCMA initiatives are intertwined in both policy and project creation, and how this confluence is creating potentials for maladaptive ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 46 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Past exposure to climate-related disaster increases the degree of P-I, which in turn drives farmers to undertake adaptation actions [14,15]. While some studies stressed the benefits of autonomous adaptation, other studies reported that it ultimately results in unintended maladaptive outcomes, such as increasing the farmer's vulnerability to CC, shifting the vulnerability to other stakeholders or sectors, and decreasing the quality of common pooled resources [16][17][18][19]. Thus, assessing a farmer's P-I toward CC is essential in two aspects: First, it provides valuable information about the efforts to encourage autonomous adaptation; second, it provides crucial insight into the effort to avoid maladaptation practices.…”
Section: Introductionmentioning
confidence: 99%
“…Past exposure to climate-related disaster increases the degree of P-I, which in turn drives farmers to undertake adaptation actions [14,15]. While some studies stressed the benefits of autonomous adaptation, other studies reported that it ultimately results in unintended maladaptive outcomes, such as increasing the farmer's vulnerability to CC, shifting the vulnerability to other stakeholders or sectors, and decreasing the quality of common pooled resources [16][17][18][19]. Thus, assessing a farmer's P-I toward CC is essential in two aspects: First, it provides valuable information about the efforts to encourage autonomous adaptation; second, it provides crucial insight into the effort to avoid maladaptation practices.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [42] "maladaptation happens when short-term strategies increase vulnerability in the long term" [43] Barnett and O'Neill [3,8,44] "action taken ostensibly to avoid or reduce vulnerability to climate change that impacts adversely on, or increases the vulnerability of other systems, sectors or social groups" [7,15,16,26,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Table 1. Cont.…”
Section: Sources Of Definitions Maladaptation Defined In Literatures Cited By Authorsmentioning
confidence: 99%
“…Another adaptation dichotomy includes judging "good" and "bad" adaptation and leads to an almost systematic opposition between adaptation and maladaptation [32]. In essence, maladaptation describes an action that results in undesirable and unintended outcome(s), and eventually increases exposure and vulnerability [10,20,34,35]. However, most of the time, there is a very fine line between success and failure, depending for example on the group of population (adaptation for who?…”
Section: Point Of Departurementioning
confidence: 99%